Program pengajaran kolaboratif mahasiswa kkm melalui peningkatan kualitas pembelajaran, pengembangan potensi siswa, dan program perpustakaan atraktif di sdn jodipan - Yusuf, Fajar Muhammad; Abror, Muhammad Syahrul; Al Farabi, Moh. Fakhran; Nadhiroh, Tahta Alfi; Muthmainnah, Luthfiyatul (Maliki Interdisciplinary Journal, 2026)
The Community Service Program (KKM) is a form of community engagement that plays a strategic role in supporting the improvement of educational quality in elementary schools. This article aims to describe and analyze the implementation of a collaborative teaching program conducted by KKM students at SDN Jodipan, focusing on three main aspects: improving learning quality, developing student potential, and implementing an attractive school library program. The activities were carried out through interactive learning using ice-breaking strategies, student competitions held during the 17th anniversary of SDN Jodipan as a medium for student potential development, and library arrangement and decoration to strengthen literacy culture. The results indicate increased student engagement and learning motivation, enhanced creativity and non-academic potential, and improved reading interest supported by a more comfortable and attractive library environment. This program demonstrates that collaboration between university students, schools, and pupils can significantly contribute to improving learning quality and strengthening literacy culture in elementary education.